2016
DOI: 10.1007/s11845-016-1442-6
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle risk factors for cardiovascular disease and diabetic risk in a sedentary occupational group: the Galway taxi driver study

Abstract: Lifestyle risk factors for CVD and dysglycaemia are prevalent amongst Irish taxi drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
12
1
1
Order By: Relevance
“…Accordingly, more than half of the participants suffered from HTN (59.8%). In this study, a higher prevalence of HTN was observed than in previous published studies that reported the prevalence of HTN within the range of 18.2% and 57% [8,27,[29][30][38][39][40][41]. Furthermore, the comparison of the results of the present study with other studies that investigated the prevalence of HTN among other professional drivers, including suburban, bus, and truck drivers, showed that the prevalence of HTN was significantly higher in taxi drivers than in other professional drivers [28,[32][33][42][43][44][45][46].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Accordingly, more than half of the participants suffered from HTN (59.8%). In this study, a higher prevalence of HTN was observed than in previous published studies that reported the prevalence of HTN within the range of 18.2% and 57% [8,27,[29][30][38][39][40][41]. Furthermore, the comparison of the results of the present study with other studies that investigated the prevalence of HTN among other professional drivers, including suburban, bus, and truck drivers, showed that the prevalence of HTN was significantly higher in taxi drivers than in other professional drivers [28,[32][33][42][43][44][45][46].…”
Section: Discussioncontrasting
confidence: 61%
“…Next, a similar number of participants were selected from each study area (about 74 drivers in each area). We determined the sample size according to formula 1 as follows: [1] Where indicates the required sample size at the 95% level of significance, represents the prevalence of HTN among the taxi drivers, which is set at 0.4 according to the previous studies [8,27,[29][30][38][39][40][41], and is the degree of precision set at 0.05. Accordingly, the sample size consisted of 369 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…More than half of ride-hailing drivers (53.2%, Table 2) in the study were overweight, much higher than the national average of 42.1% [57] . Some studies have shown that obesity and smoking, both as in uencing factors of a variety of diseases, can increase the risk of cardiovascular and cerebrovascular diseases among drivers [58,59] . When it comes to the relationship between smoking and obesity, it is very complicated.…”
Section: Obesity and Smokingmentioning
confidence: 99%
“…It was also reported that the CVD risk is particularly high in middle-aged people at 40–59 years [ 11 ]. Due to sedentary behavior, taxi drivers have a high obesity rate [ 15 ], and they are reported as a representative CVD risk group [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%